ENANTIOSPECIFIC SYNTHESES OF 2S,3R,4R,5S-TRIHYDROXYPIPECOLIC ACID, 2R,3R,4R,5S-TRIHYDROXYPIPECOLIC ACID, 2S,4S,5S-DIHYDROXYPIPECOLIC ACID, AND BULGECININE FROM DEUTERIUM-GLUCURONOLACTONE - Bashyal, B; Chow, H; Fleet, G (1986)
The potential of D-glucuronolactone as a starting material for the synthesis of polyfunctional amino acids is illustrated by its conversion to 2S,3R,4R,5S-trihydroxypipecolic acid, 2R,3R,4R,5S-trihydroxypipecolic acid, 2S,4S,5S-dihydroxypipecolic acid, and bulgecinine. © 1986.